Association between opioid therapy trajectories and potential opioid‐related adverse health events. Issue 10 (30th June 2022) - Hayes, Corey J.; Koonce, Ruston M.; Gressler, Laura Elisabeth; Hu, Bo; Williams, James Silas; Martin, Bradley C.
Abstract: Purpose: We identified associations between membership in seven group‐based trajectories based on supply of filled opioid prescriptions and potential opioid‐related adverse health events over a 720‐day window. Methods: We identified two veteran cohorts with chronic non‐cancer pain who initiated treatment with long‐term opioid therapy between 2008 and 2015, excluding those with prior substance use disorder ( n  = 373 941) or non‐SUD, opioid‐related adverse outcome ( n  = 405 631) diagnoses. Outcomes of interest included opioid use disorder, non‐opioid drug use disorder, and alcohol use disorder for the first cohort; or accidents resulting in wounds or injuries, self‐inflicted injuries, opioid‐related accidents and overdoses, alcohol and non‐opioid drug‐related accidents and overdoses, and violence‐related injuries for the second cohort. Using a cross‐sectional design, Veterans were followed until the specific outcome of interest was diagnosed, they died, the study ended, or they were lost to follow up. Accelerated failure time models were estimated for each outcome. Results: Membership in persistent moderate days covered and persistent modest days covered trajectories was associated with decreased risk of opioid use disorder (Moderate: θ = 0.59, 95%CI:0.54, 0.64; Modest: θ = 0.54, 95%CI:0.50, 0.59) and opioid overdose (Moderate: θ = 0.67, 95%CI: 0.57, 0.79; Modest: θ = 0.72, 95%CI:0.61, 0.85) versus higher‐utilizing persistent users. Rapid discontinuation was associated with decreased risk of opioid use disorder (θ = 0.86, 95% CI:0.77, 0.95) and opioid overdose (θ = 0.54, 95%CI:0.41, 0.71), but increased risk of alcohol use disorder (θ = 1.07, 95%CI:1.00, 1.15) and other substance use disorders. Delayed discontinuation or delayed reduction was associated with increased risk for most opioid related adverse health events. Conclusion: Persistent use trajectories with low levels of opioid utilization were associated with lower risks of potential opioid‐related adverse health events.